Lair of the Wolven : Mine - Book 3 - Ward, J. R., 1969- (New York : Pocket Books, 2024)
"In this finale, Lydia and Daniel are bracing themselves for his inevitable decline but first, they must go on a rescue mission that will put both their lives in danger."- -
Keywords: Wolves -- Fiction; Man-woman relationships -- Fiction; Shapeshifting -- Fiction; Environmentalists -- Fiction; Paranormal fiction; Fantasy fiction; Romance fiction